2018
DOI: 10.1155/2018/5823230
|View full text |Cite
|
Sign up to set email alerts
|

To Study the Effect of the Generating Polynomial on the Quality of Nonlinear Components in Block Ciphers

Abstract: Substitution box ( -box), being the only nonlinear component, contributes to the confusion creating capability of a cryptosystem. Keeping in view the predominant role of -box, many design algorithms to synthesize cryptographically stronger -boxes have gained pivotal attention. A quick review of these algorithms shows that all these ideas mainly concentrate on the choice of bijective Boolean functions, with nonobservance to the irreducible polynomial that generates the Galois field. In this paper, we propose th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Enhancement in nonlinearity (NL) value of initial S-box using dynamic permutation approach with respect to computation time is depicted in Figure 3. Although many authors suggested new methods to construct S-Box having nonlinearity>=112 like AES, these approaches lack one or more security criteria like non-bijectiveness [77], the existence of fixed points [45,78,79,80,81], high value of differential probability [82], static permutation [83], usage of fixed irreducible polynomial by [80,83] and AES, complex construction process [82], etc. Our proposed scheme for construction of S-box uses simple and novel dynamic transformation being the first one of its nature, employs dynamic affine transformation using modular multiplicative inversion as compared to the static affine transformation used in many of the above mentioned techniques employing complex GF inversion process, and a new dynamic permutation procedure in comparison to the static permutation utilized in these methods.…”
Section: G Fixed Points Analysis (Fpa)mentioning
confidence: 99%
“…Enhancement in nonlinearity (NL) value of initial S-box using dynamic permutation approach with respect to computation time is depicted in Figure 3. Although many authors suggested new methods to construct S-Box having nonlinearity>=112 like AES, these approaches lack one or more security criteria like non-bijectiveness [77], the existence of fixed points [45,78,79,80,81], high value of differential probability [82], static permutation [83], usage of fixed irreducible polynomial by [80,83] and AES, complex construction process [82], etc. Our proposed scheme for construction of S-box uses simple and novel dynamic transformation being the first one of its nature, employs dynamic affine transformation using modular multiplicative inversion as compared to the static affine transformation used in many of the above mentioned techniques employing complex GF inversion process, and a new dynamic permutation procedure in comparison to the static permutation utilized in these methods.…”
Section: G Fixed Points Analysis (Fpa)mentioning
confidence: 99%
“…In [ 17 ], the authors proposed two different S-boxes for AES by modifying the affine transformation matrices. In [ 18 , 19 ], the authors proposed a variable and dynamic S-box mapping for AES using different irreducible polynomials. Thus, a different S-box is generated in each round of AES, which enhances the security of AES but only generates a limited number of S-boxes.…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [46] proposed two different S-boxes instead of one AES S-box by modifying the affine transformation matrices that are used alternatively in the algorithm. In [47], [48] the authors proposed a variable mapping S-boxes for AES. Using secret key as well as using different irreducible polynomials produce dynamic S-boxes.…”
Section: Introductionmentioning
confidence: 99%